Cardiac electrophysiology consultative experience at the epicenter of the COVID-19 pandemic in the United States - Jeremy P. Berman; Mark P. Abrams; Alexander Kushnir; Geoffrey A. Rubin; Frederick Ehlert; Angelo Biviano; John P. Morrow; Jose Dizon; Elaine Y. Wan; Hirad Yarmohammadi; Marc P. Waase; David A. Rubin; et al. (Indian Pacing and Electrophysiology Journal, 2020)
Background: The COVID-19 pandemic has greatly altered the practice of cardiac electrophysiology around the world for the foreseeable future. Professional organizations have provided guidance for practitioners, but real-world examples of the consults and responsibilities cardiac electrophysiologists face during a surge of COVID-19 patients is lacking. Methods: In this observational case series we report on 29 consecutive inpatient electrophysiology consultations at a major academic medical center in New York City, the epicenter of the pandemic in the United States, during a 2 week period from March 30-April 12, 2020, when 80% of hospital beds were occupied by COVID-19 patients, and the New York City metropolitan area accounted for 10% of COVID-19 cases worldwide. Results: Reasons for consultation included: Atrial tachyarrhythmia (31%), cardiac implantable electronic device management (28%), bradycardia (14%), QTc prolongation (10%), ventricular arrhythmia (7%), post-transcatheter aortic valve replacement conduction abnormality (3.5%), ventricular pre-excitation (3.5%), and paroxysmal supraventricular tachycardia (3.5%). Twenty-four patients (86%) were positive for COVID-19 by nasopharyngeal swab. All elective procedures were canceled, and only one urgent device implantation was performed. Thirteen patients (45%) required in-person evaluation and the remainder were managed remotely. Conclusion: Our experience shows that the application of a massive alteration in workflow and personnel forced by the pandemic allowed our team to efficiently address the intersection of COVID-19 with a range of electrophysiology issues. This experience will prove useful as guidance for emerging hot spots or areas affected by future waves of the pandemic.